Knowledge Attitude and Practices of Mitanin's (Community Health Workers) in Chhattisgarh: Malaria Elimination Perspective - Ranjha, Raju; Yadav, Chander Prakash; Chourasia, Mehul Kumar; Nitika,; Dash, Chinmay Kumar; Kumar, Jitendra (Frontiers in Public Health, 2022)
Background For the success of any program, its implementation plays a crucial role. Community health workers are of immense importance for malaria elimination from India. Objective This study was aimed to assess the knowledge gaps and the responsible factors for mitanins' knowledge on various aspects of and problems faced by mitanins during their work. Methods Structured interviewer-based questionnaire was used to collect the data, and ordinal regression was applied to analyze the data. Results Only 26% of the mitanins were having a good knowledge attitude and practices (KAP) score about malaria. Malaria endemicity of area [odds ratio (OR) = 0.26, 95% CI = 0.13–0.50), P < 0.001] and education (OR = 0.35, 95% CI = 0.18–0.69, P = 0.002) were the two significant factors affecting the KAP of mitanins. Conclusion: This study shows that prioritizing education while recruiting the mitanins and training them in the low endemic areas with a focus on malaria, which will help achieve the malaria elimination goal.